Managing risk in high-stakes faculty employment decisions - Flood, Julee T.; Leap, Terry L., 1948- (ILR Press, an imprint of Cornell University Press, 2018)
"Analyzes the risks associated with the social-psychological, contractual, and constitutional issues affecting faculty hiring, promotion, and tenure decisions"--